Comparative morphology and floral biology of three species of the genus of Nymphaea from Bangladesh - Begum, Hosne Ara; Ghosal, KK; Chattopadhyay, TK (Bangladesh Journal of Botany, 2011)
Morphology and floral biology of three species of the genus Nymphaea (Nymphaeaceae) of Bangladesh revealed that N. nouchali, N. pubescens and N. rubra, were normal, protogynous or normal and protogynous, respectively. N. pubescens was night bloomer and each flower opened for three consecutive nights where as N. rubra opened for four consecutive nights and N. nouchali for three consecutive days. The behavior of anther dehiscence and stigma appendages had significant role in pollination. Excellent pollen germination and receptivity were observed in the exudate of stigma cup. Key words: Nymphaea; Comparative morphology; Floral biology DOI: 10.3329/bjb.v39i2.7478 Bangladesh J. Bot. 39(2): 179-183, 2010 (December)